Removing physiological motion from intravital and clinical functional imaging data - Warren, Sean C; Nobis, Max; Magenau, Astrid; Mohammed, Yousuf H; Herrmann, David; Moran, Imogen; Vennin, Claire; Conway, James RW; Mélénec, Pauline; Cox, Thomas R; Wang, Yingxiao; Morton, Jennifer P; et al. (eLife, 2018)
Intravital microscopy can provide unique insights into the function of biological processes in a native context. However, physiological motion caused by peristalsis, respiration and the heartbeat can present a significant challenge, particularly for functional readouts such as fluorescence lifetime imaging (FLIM), which require longer acquisition times to obtain a quantitative readout. Here, we present and benchmark Galene, a versatile multi-platform software tool for image-based correction of sample motion blurring in both time resolved and conventional laser scanning fluorescence microscopy data in two and three dimensions. We show that Galene is able to resolve intravital FLIM-FRET images of intra-abdominal organs in murine models and NADH autofluorescence of human dermal tissue imaging subject to a wide range of physiological motions. Thus, Galene can enable FLIM imaging in situations where a stable imaging platform is not always possible and rescue previously discarded quantitative imaging data.
Keywords: FLIM; FRET; motion correction; intravital microscopy; multiphoton